2008
DOI: 10.1016/j.micinf.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Brucella abortus OPS dictating uptake and restricting NF-κB activation in murine macrophages

Abstract: Smooth Brucella abortus S2308 is virulent while rough derivatives are attenuated. Intracellular killing is often blamed for these differences. In the studies described, uptake kinetics and interaction of S2308 and S2308 manBA::Tn5 (CA180) rough mutants with macrophages were investigated. The results revealed that smooth B. abortus was rapidly internalized, achieving a maximum level in less than 5 minutes without additional uptake over the next 30 minutes. In contrast, continued uptake of the rough mutant was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 38 publications
(71 reference statements)
3
47
1
Order By: Relevance
“…Hence, we expected to determine the impact of the distinct signaling pathways associated with TLR4/JAK2 on phagocytic mechanisms of Brucella. Some studies have revealed that TLR4 is important for Brucella uptake and cellular responses in macrophages (14,24). In this study, we showed that the internalization of B. abortus is strongly suppressed by the disruption of TLR4.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Hence, we expected to determine the impact of the distinct signaling pathways associated with TLR4/JAK2 on phagocytic mechanisms of Brucella. Some studies have revealed that TLR4 is important for Brucella uptake and cellular responses in macrophages (14,24). In this study, we showed that the internalization of B. abortus is strongly suppressed by the disruption of TLR4.…”
Section: Discussionsupporting
confidence: 50%
“…Ligation of TLR4 promotes the activation of complex signaling pathways, including mitogen-acti-functions, including phagocytosis (23). Nevertheless, the downstream signaling cascades subsequent to the entry of B. abortus into epithelial cells (3,9) and murine macrophages (24) have not been fully elucidated.…”
mentioning
confidence: 99%
“…1) (7), another way to compare macrophage responses to rough and smooth brucellae is to use differential MOIs (roughly 10-fold difference) for the initial infection to achieve the same Brucella cells taken up by macrophages. However, this method ignores the potential influence of extracellular brucellae on the macrophage responses (e.g., Toll-like receptor 4 [TLR4] activation) (31). Those brucellae outside macrophages may interact with the macrophage cell surface proteins or other factors and trigger active macrophage responses.…”
Section: Resultsmentioning
confidence: 99%
“…88 Moreover, the replication of B. abortus S19 strain and S2308 strain in vivo has also been demonstrated to be TLR4-independent. 89 Interestingly, Pei et al 90 have demonstrated that TLR4 is involved in the internalization of smooth B. abortus in macrophages. 90 Of note, a recent study using unlipidated outer membrane protein 16 of B. abortus indicated that the production of pro-inflammatory cytokines induced by this unlipidated protein is TLR4-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…89 Interestingly, Pei et al 90 have demonstrated that TLR4 is involved in the internalization of smooth B. abortus in macrophages. 90 Of note, a recent study using unlipidated outer membrane protein 16 of B. abortus indicated that the production of pro-inflammatory cytokines induced by this unlipidated protein is TLR4-dependent. 80 In our study, high levels of antigen-specific Th1-type cytokines such as IFN-c and IL-2 and high levels of protection against B. abortus infection were observed in wild-type mice vaccinated with the rBCSP31 vaccine compared with these parameters in TLR2 2/2 and TLR4 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%